Helicobacter pylori and Its Genome: Lessons from the Treasure Map - Diane E Taylor (Canadian Journal of Gastroenterology)
The availability of the complete genome sequence of Helicobacter pylori 26695 has opened new avenues for research in the molecular biology of this gastric pathogen. The present review gives a general overview of H pylori obtained from the complete genome sequence and compares this with data previously obtained from cloning and functional studies of H pylori. The cagA pathogenicity island of 40 kilobases, which encodes a type IV secretion system, is discussed. The diversity of H pylori genomes is well known, yet new data indicate that some aspects of the genome, particularly outer membrane protein genes, are conserved. Genes encoding proteins involved in molecular mimicry between bacterium and gastric epithelial tissue, specifically those encoding Lewis X and Lewis Y antigens, are discussed. The large number of DNA restriction and modification genes and their role in H pylori infection are considered. Finally, gene transfer is discussed. The availability of the complete genome sequence of H pylori 26695 and the soon to be available sequence of J99 will speed up and assist in the analysis of H pylori genes and their encoded proteins. The genomes of both strains will be useful as references with which other H pylori genomes can be compared.